Comment on Yeste et al. Polyphenols and IUGR Pregnancies: Intrauterine Growth Restriction and Hydroxytyrosol Affect the Development and Neurotransmitter Profile of the Hippocampus in a Pig Model. Antioxidants 2021, 10, 1505 - Glòria Garrabou; Ana Sandra Hernández; Mariona Guitart-Mampel; Elena Escalada-Casellas; Gemma Malats-Revelles; Sara Castro-Barquero; Ana María Ruiz-León; Kilian Vellvé; Rosa Casas; Francesc Cardellach; Fàtima Crispi; Francesc Josep García-García (MDPI AG, 2022)
Intrauterine growth restriction (IUGR) affects 5-10% of newborns and increases the risks of intrauterine demise, neonatal morbidity, and death. In their recent publication, Yeste et al. found the benefits of hydroxytyrosol supplementation on brain remodeling from an IUGR pig model. Additionally, we found a significant decrease in phenolic alcohol (tyrosol and hydroxytyrosol) intake in IUGR pregnant women. Altogether, these findings support the notion that dietetic interventions, through supplementation but mostly via a balanced diet, can ameliorate IUGR complications. Furthermore, diet intervention combined with early biomarkers may allow clinicians to eventually anticipate IUGR diagnosis and help avoid one of the most frequent causes of newborn mortality and morbidity.